(untitled) (Kindle, 2022)
In vitro investigations have revealed that consumption of selenium can considerably decrease the expression of IFN-g in Th1 cells. A low plasma selenium content has been shown amongst cases with any of a variety of disorders, including autoimmune diseases, although neither the reason for this anomaly nor its possible functional importance are known. The seleno-enzyme glutathione peroxidase has role in the antioxidant defence by reacting with hydrogen peroxide and related compounds. Different oxygen radicals may have role in the pathogenesis of autoimmune disseases, and the accumulation of lipid peroxidation products in body fluids has been shown. In mammals, selenium is covalently bound commonly in selenocysteine moieties in proteins, and in human tissue glutathione peroxidase is the only selenoprotein hitherto found. In a previous investigation, most of the selenium in human plasma was shown to be located in selenoproteins other than glutathione peroxidase. Few other investigations on selenium localization in human tissue have been carried out, one reason probably being the difficulty in indicating the low selenium levels present in biological material.